Организация обучения русскому языку иностранных студентов-филологов в Харьковском национальном университете имени В.Н. Каразина - Ушакова, Н.И.; Доценко, Н.П.; Ильина, Л.Э.; Мисенева, В.В.; Чжу, Ин; Ушакова, Н.І.; Бєй, Л.Б.; Доценко, Н.П.; Ільїна, Л.Е.; Місеньова, В.В.; Чжу, Ін; Ushakova, N.I.; et al. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2011)
Статья посвящена принципам организации обучения иностранных студентов-филологов русскому языку как второму иностранному , описана реализация требований новой образовательной парадигмы в модульной программе для студентов факультета иностранных языков.
Організація навчання російської мови іноземних студентів-філологів у Харківському національному університеті імені В.Н. Каразіна.
Organization of Teaching Foreign Students-Philologists the Russian Language at V.N. Karazin Kharkov National University
The article is devoted to the principles of organizing the process of teaching foreign students-philologists the Russian language as a second foreign one; the implementation of new educational paradigm demands in the Module Academic Program worked out for the students of the foreign language department has been described.
Keywords: foreign students-philologists; Russian language; second foreign language; Module Academic Program; иностранные студенты-филологи; русский язык; второй иностранный язык; модульная программа; іноземні студенти-філологи; російська мова; друга іноземна мова; модульна программа